The association between social engagement and depressive symptoms in middle-aged and elderly Chinese: A longitudinal subgroup identification analysis under causal inference frame - Yang, Yuhui; Li, Yemian; Zhao, Peng; Wang, Jingxian; Mi, Baibing; Pei, Leilei; Zhao, Yaling; Chen, Fangyao (Frontiers in Aging Neuroscience, 2022)
Abstract Background: Studies have suggested that there is a significant association between social engagement and depression symptoms. However, this association may differ in people with different features such as different sociodemographic characteristics and health conditions. Methods: Research data was obtained from the CHARLS database. The causal inference was performed with the propensity score. We used the linear mixed-effects model tree algorithm under the causal inference frame for subgroup identification analysis. Results: We included 13,521 participants and the median follow-up time is 4 years. Under the casual inference frame, the association between social engagement and depression symptoms is confirmed for all included individuals (OR=0.957, P=0.016; 95%CI: 0.923-0.992). Using the linear mixed-effects model tree, we found two subgroups, including middle-aged and elderly residents who live in rural areas with less than 6 hours of sleep and those living in urban areas, could benefit more from social engagement. After using the propensity score method, all the two subgroups selected are statistically significant (P=0.007; P=0.013) and have a larger effect size (OR=0.897, 95%CI: 0.830-0.971; OR=0.916, 95%CI: 0.854-0.981) than the whole participants. As for sex difference, this associations are statistically significant in male (OR: 0.935, P=0.011, 95%CI: 0.888-0.985) but not in female (OR: 0.979, P=0.399, 95%CI: 0.931-1.029). Conclusions: Our findings indicate that social engagement may reduce the risks of depressive symptoms among all individuals. The identified subgroups of middle-aged and elderly residents who live in rural areas with less than 6 hours of sleep and those who live in urban areas may benefit more from the social engagement than the whole participants.